Potret Praktik Manajemen Sekolah Islam Terpadu di SDIT Ikhtiar Makassar: Portrait of Integrated Islamic School Management Practices at SDIT Ikhtiar Makassar - Arifin, Inayah az zahra; Agustin; Ahlunansar; Arismunandar; Amaliah (Pendidikan Al-Gafari, 2025)
This research examines the management practices of Integrated Islamic Schools (IIS) at SDIT Ikhtiar Makassar as a concrete example of the implementation of the IIS model in Indonesia. This research aims to understand how SDIT Ikhtiar Makassar integrates Islamic values into all aspects of learning, identify the factors that support and hinder the implementation of the IIS model at the school, and formulate effective strategies to improve the quality of education at SDIT Ikhtiar Makassar. This research uses a qualitative descriptive method by collecting data through in-depth interviews with the principal and participant observation in the school environment. The research findings show that SDIT Ikhtiar Makassar has successfully integrated Islamic values into the curriculum, teaching methods, and extracurricular activities. The school also involves all stakeholders, including parents, teachers, and the community, in supporting internal quality assurance. However, the school faces financial challenges that are addressed by offering various payment schemes and collaborating with various parties. The research concludes that the IIS model at SDIT Ikhtiar Makassar has the potential to improve the quality of education in Indonesia, but further efforts are needed to address the challenges faced, particularly in terms of funding and stakeholder management.